Perceived Health Contributes to the Attractiveness of Facial Symmetry, Averageness, and Sexual Dimorphism - Gillian Rhodes; Sakiko Yoshikawa; Romina Palermo; Leigh W. Simmons; Marianne Peters; Kieran Lee; Jamin Halberstadt; John R. Crawford (2007)
Symmetry, averageness, and sexual dimorphism (femininity in female faces, masculinity in male faces) are attractive in faces. Many have suggested that preferences for these traits may be adaptations for identifying healthy mates. If they are, then the traits should be honest indicators of health and their attractiveness should result from their healthy appearance. Much research has focused on whether these traits honestly signal health. Here we focused on whether the appeal of these traits results from their healthy appearance. Specifically, we tested whether the attractiveness of symmetry, averageness, and sexual dimorphism is reduced or eliminated when perceived health is controlled, in two large samples of Western faces and a large sample of Japanese faces. The appeal of symmetric faces was largely due to their healthy appearance, with most associations between symmetry and attractiveness eliminated when perceived health was controlled. A healthy appearance also contributed to the appeal of averageness and femininity in female faces and masculinity in male faces, although it did not fully explain their appeal. These results show that perceptions of attractiveness are sensitive to a healthy appearance, and are consistent with the hypothesis that preferences may be adaptations for mate choice.